2020
DOI: 10.1037/pro0000354
|View full text |Cite
|
Sign up to set email alerts
|

Development and refinement of educational materials to help older veterans use VA mental health mobile apps.

Abstract: Many older Veterans own smartphones, yet may need assistance learning to use them and about available mental health mobile apps. Our educational materials developed using user-centered design methods address these needs and may increase awareness about free VA mental health resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Connolly and colleagues [ 17 ] found that rural veterans are more likely to oppose app usage, describe smartphones as hard to navigate, and cite barriers to usage compared to urban-dwelling populations. However, educational materials and training programs can be successfully implemented to increase older veterans’ comfort with using apps and overcome barriers to utilization [ 27 , 28 ]. With additional efforts to promote comfort with and confidence in mental health apps, they may be a scalable, accessible, and helpful resource for older veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Connolly and colleagues [ 17 ] found that rural veterans are more likely to oppose app usage, describe smartphones as hard to navigate, and cite barriers to usage compared to urban-dwelling populations. However, educational materials and training programs can be successfully implemented to increase older veterans’ comfort with using apps and overcome barriers to utilization [ 27 , 28 ]. With additional efforts to promote comfort with and confidence in mental health apps, they may be a scalable, accessible, and helpful resource for older veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Five papers cited age-specific barriers to digital learning ( Arthanat et al, 2019 ; Brown & Strommen, 2018 ; Gould et al, 2020 ; LoBuono et al, 2019 ; Tomczyk et al, 2020 ). The notion of subjective aging arose and how this may predict learning outcomes ( Brown & Strommen, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Step-by-Step App Guides were developed for PTSD Coach, Mindfulness Coach, and Mood Coach (see Gould et al, 2020b ). Due to Mood Coach only being available on iOS devices, a limited number were printed and disseminated.…”
Section: Methodsmentioning
confidence: 99%
“…To address this potential implementation gap with regard to digital literacy and awareness of VA mental health apps, we developed patient education materials aimed toward older (or novice) users of mobile devices (Gould et al, 2020b ). The materials, designed using an iterative User-Centered Design approach, teach the basics of mobile devices, explain how to download an app, and provide step-by-step guides to three VA mental health self-management apps (PTSD Coach, Mindfulness Coach, Mood Coach).…”
mentioning
confidence: 99%